On the Yehi Raẓon Formula in the Blessing for the New Month in the Ashkenazic Rite - Arend, Aharon (2021)
In the early custom of Ashkenaz, on the Shabbat preceding the beginning of the month, the coming of the new month (Rosh Ḥodesh) would be announced after the reading from the Torah and before the Torah scroll was returned to the synagogue's Holy Ark. The ritual included reciting the paragraph beginning with the words mi she-‘asah nissim (may He who performed miracles) and continuing with an announcement of the timing of Rosh Ḥodesh. In the second half of the eighteenth century, an addition to the liturgy appeared before the Mi She-‘asah Nissim section: a passage beginning yehi raẓon (may it be Your will) that the Babylonian Talmud relates was recited daily by the sage Rav following the Amidah prayer. This article suggests some reasons for the addition of the passage, traces the spread of the practice of its recitation among Ashkenazic communities, and concludes with an examination and explanation of two apparently erroneous additions to the Yehi Raẓon formula.